CHEMICAL COMPOSITION ANALYSIS OF FRESHWATER MUSSEL (Pilsbryoconcha exilis) - Alghifary, Zaki; Edison, Edison; Diharmi, Andarini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTFreshwater mussel is a type of shellfish that is popular with the community and has high nutritional value. This study aims to determine the chemical composition of mussel meat. The method used in this study was an experiment which was carried out in two stages, namely 1) preparation of mussel and 2) analysis of the chemical composition of mussel meat. The parameters measured in this study include the proportion of body parts and analysis of the chemical composition of the meat consisting of water, ash, fat, protein and carbohydrate content (by difference). The results showed that mussel meat had a body part proportion of 17.75% and the chemical composition produced by mussel meat was 78.46% water content (bb), 11.87% ash (bk), 7.51% fat (bk). , protein 78.87% (bk), and carbohydrates (by difference) 1.75% (bk).Keywords: Freshwater mussel, Chemical composition, Body proportion